Silicon-based lithium ion battery negative electrode sheet and preparation method and application thereof

CN122907578APending Publication Date: 2026-10-13安徽得壹能源科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610699217.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-20
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

然而,硅材料作为锂离子电池负极材料时,在重复充放电过程中会存在较大体积膨胀、不稳定的固体电解质界面(SEI)增长、低初始库仑效率、低面积容量和安全问题等,导致电化学性能下降,阻碍了硅负极材料的商业应用

Benefits of technology

本发明提供了一种硅基锂离子电池负极片,其以集流体为基体,依次在集流体的表面叠层设计第一碳层、硅碳复合层、第二碳层和氮化钛层;其中,硅碳复合层由多层交替的硅层和碳层组成。该硅基锂离子电池负极片中通过硅碳交替层能够有效缓解硅的体积膨胀、导电性能差以及提升电极的首次库仑效率;通过设置第一碳层和第二碳层以及硅碳复合层能够建立电子快速传输通道,提升电解的倍率性能,通过设置氮化钛层能够为人工SEI膜,能有效隔离电解液与内部的硅,防止副反应发生,同时优异的机械强度能抵抗硅膨胀带来的冲击,维持界面稳定。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application relates to the technical field of lithium ion batteries, in particular to a silicon-based lithium ion battery negative plate and a preparation method and application thereof. The silicon-based lithium ion battery negative plate takes a current collector as a base body, and a first carbon layer, a silicon-carbon composite layer, a second carbon layer and a titanium nitride layer are sequentially designed on the surface of the current collector; the silicon-carbon composite layer is composed of multiple layers of alternating silicon layers and carbon layers. In the silicon-based lithium ion battery negative plate, the alternating silicon-carbon layers can effectively alleviate the volume expansion of silicon, improve the poor conductivity of silicon and improve the initial coulomb efficiency of the electrode; the first carbon layer and the second carbon layer and the silicon-carbon composite layer can establish an electronic rapid transmission channel, improve the rate performance of electrolysis, the titanium nitride layer can form an artificial SEI film, effectively isolate the electrolyte from the internal silicon, prevent the occurrence of side reactions, and the excellent mechanical strength can resist the impact caused by the expansion of silicon and maintain the stability of the interface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion battery technology, specifically to a silicon-based lithium-ion battery negative electrode sheet, its preparation method, and its application. Background Technology

[0002] With the rapid development of electronic products, large-scale energy storage and electric vehicles, the development of lithium-ion batteries with high energy density, high power density, long cycle life and high safety has become a research hotspot in the field of energy storage. Developing electrode materials with high capacity, high rate and high stability is an important way to achieve this goal.

[0003] In the field of lithium-ion batteries, the theoretical specific capacity of commercially available graphite anodes is only 372 mAh g. -1 However, this makes it difficult to meet people's requirements for the high energy density of lithium-ion batteries. Silicon, due to its high theoretical capacity (4200mAh g / g), is an alternative. -1 Silicon has been widely studied due to its advantages such as low lithiation potential (+) and abundant reserves. However, when silicon is used as an anode material for lithium-ion batteries, it suffers from significant volume expansion, unstable solid electrolyte interface (SEI) growth, low initial coulombic efficiency, low areal capacity, and safety issues during repeated charge and discharge processes, leading to a decline in electrochemical performance and hindering the commercial application of silicon anode materials. Summary of the Invention

[0004] To overcome the above problems, the present invention provides a silicon-based lithium-ion battery negative electrode sheet, its preparation method and application.

[0005] To achieve the above technical objectives, the present invention adopts the following technical solution: In a first aspect, the present invention provides a silicon-based lithium-ion battery negative electrode sheet, which uses a current collector as a substrate and sequentially stacks a first carbon layer, a silicon-carbon composite layer, a second carbon layer and a titanium nitride layer on the surface of the current collector. The silicon-carbon composite layer consists of multiple alternating silicon and carbon layers.

[0006] In one or more embodiments, the current collector is one of copper foil, nickel foil, copper foam, or nickel foam, preferably copper foil.

[0007] In one or more embodiments, the silicon-carbon composite layer has an alternation period of 8 to 12 cycles between the silicon and carbon layers, and the total thickness of the silicon-carbon composite layer is 70 to 200 nm. Too few cycles result in insufficient buffering, while too many cycles affect the capacity.

[0008] Preferably, the thickness of the silicon layer is 8-12 nm and the thickness of the carbon layer is 2-3 nm in each alternation cycle. When the silicon layer is too thick, its volume expansion is too large, leading to problems such as pulverization and cracking.

[0009] In one or more embodiments, the thickness of the first carbon layer is 4 to 6 nm, preferably 5 nm.

[0010] In one or more embodiments, the thickness of the second carbon layer is 4 to 6 nm, preferably 5 nm.

[0011] In one or more embodiments, the thickness of the titanium nitride layer is 20~50 nm.

[0012] A second aspect of the present invention provides a method for preparing the silicon-based lithium-ion battery negative electrode sheet described in the first aspect, comprising the following steps: A first carbon layer, a silicon-carbon composite layer, a second carbon layer, and a titanium nitride layer are magnetron sputtered onto the surface of the current collector.

[0013] In one or more embodiments, a method for magnetron sputtering a silicon-carbon composite layer on the surface of a first carbon layer includes: A silicon-carbon composite layer is obtained by sequentially magnetron sputtering a silicon layer and a carbon layer on the surface of the first carbon layer, followed by repeated alternating magnetron sputtering of the silicon and carbon layers.

[0014] Preferably, the number of alternation periods between the silicon layer and the carbon layer is 8 to 12.

[0015] A third aspect of the present invention provides a lithium-ion battery comprising the silicon-based lithium-ion battery negative electrode sheet described in the first aspect or the silicon-based lithium-ion battery negative electrode sheet prepared by the preparation method described in the second aspect.

[0016] The beneficial effects of this invention are as follows: This invention provides a silicon-based lithium-ion battery anode sheet, which uses a current collector as a substrate and sequentially stacks a first carbon layer, a silicon-carbon composite layer, a second carbon layer, and a titanium nitride layer on the surface of the current collector; wherein, the silicon-carbon composite layer is composed of multiple alternating silicon and carbon layers. In this silicon-based lithium-ion battery anode sheet, the alternating silicon-carbon layers effectively alleviate the volume expansion and poor conductivity of silicon, and improve the first coulombic efficiency of the electrode; the first carbon layer, the second carbon layer, and the silicon-carbon composite layer establish a fast electron transport channel, improving the rate performance of the electrolyte; the titanium nitride layer acts as an artificial SEI film, effectively isolating the electrolyte from the internal silicon, preventing side reactions, and its excellent mechanical strength resists the impact of silicon expansion, maintaining interface stability. Detailed Implementation

[0017] It should be noted that the following detailed descriptions are exemplary and intended to provide further illustration of the invention. Unless otherwise specified, all technical and scientific terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.

[0018] It should be noted that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the scope of exemplary embodiments according to the invention. As used herein, the singular form is intended to include the plural form as well, unless the context clearly indicates otherwise. Furthermore, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they indicate the presence of features, steps, operations, devices, components, and / or combinations thereof.

[0019] In the field of lithium-ion batteries, the theoretical specific capacity of commercially available graphite anodes is only 372 mAh g. -1 However, this makes it difficult to meet people's requirements for the high energy density of lithium-ion batteries. Silicon, due to its high theoretical capacity (4200mAh g / g), is an alternative. -1 Silicon has been widely studied due to its advantages such as low lithiation potential (+) and abundant reserves. However, when silicon is used as an anode material for lithium-ion batteries, the following problems arise: ① During cycling, silicon materials experience mechanical stress due to volume expansion, leading to particle cracking and subsequent reaction with the electrolyte to form an unstable solid electrolyte interphase (SEI) film. This unstable SEI film not only consumes electrolyte and lithium ions but also causes irreversible capacity loss and rapid degradation of cycle performance, severely limiting the practical application of silicon-carbon materials in lithium-ion batteries.

[0020] ② Silicon itself has a low electronic conductivity, much lower than that of graphite. This leads to: obstructed electron transport within the electrode; poor rate performance (high current charge / discharge capability); and some silicon particles may be unable to participate in the reaction due to their inability to obtain electrons in time, resulting in capacity loss.

[0021] To overcome the aforementioned problems, this invention provides a silicon-based lithium-ion battery anode sheet, wherein a first carbon layer, a silicon-carbon composite layer, a second carbon layer, and a titanium nitride layer are sequentially stacked on the surface of the current collector; wherein the silicon-carbon composite layer is composed of multiple alternating silicon and carbon layers. The synergistic effect of each layer in the silicon-based lithium-ion battery anode sheet provided by this invention simultaneously overcomes the commercialization bottlenecks of silicon anodes, such as short cycle life, poor rate performance, and low initial efficiency.

[0022] Specifically, the first carbon layer, acting as the interface layer between the current collector and the active layer, effectively solves the problems of electrical contact failure and interface stress concentration between the active layer and the current collector. The first carbon layer provides a low-resistance electron channel, ensuring that electrons generated by the silicon-carbon composite layer can be quickly transferred to the current collector, thus solving the contact resistance problem caused by the poor conductivity of silicon. Furthermore, the first carbon layer acts as a buffer layer, mitigating the direct pulling on the current collector surface during the expansion of the silicon-carbon composite layer and preventing interface delamination. Simultaneously, the first carbon layer has good adhesion to the current collector and can prevent adverse alloying reactions between silicon and the current collector during high-temperature / cycling processes.

[0023] Silicon-carbon composite layers effectively solve the problems of silicon volume expansion and pulverization, poor conductivity, and crack penetration. By dividing a thick silicon layer into multiple thin silicon layers, the absolute volume expansion of a single thin silicon layer is small, making it difficult for large cracks to penetrate the entire layer. The carbon layers between the silicon layers absorb the expansion stress of adjacent silicon layers, while preventing cracks originating in one silicon layer from propagating to the next. Furthermore, the alternating carbon layers form a three-dimensional conductive framework between the silicon layers, allowing electrons to quickly "jump" through the carbon layers, bypassing the high-resistivity silicon bulk.

[0024] The second carbon layer, serving as a transition layer between the silicon-carbon composite layer and the titanium nitride layer, effectively addresses issues such as interfacial side reactions, stress transfer mismatch, and interrupted electron transport. It acts as a chemical barrier, preventing direct contact between the upper titanium nitride layer and the lower silicon layer during fabrication or cycling, thus avoiding the formation of high-resistivity titanium silicide. Furthermore, the second carbon layer functions as an additional flexible buffer layer, homogenizing the uneven expansion stress of the silicon-carbon composite layer before transferring it to the outer titanium nitride layer, preventing the outer hard film from cracking due to excessive localized stress. Moreover, the second carbon layer ensures a smooth electron transport path from the silicon-carbon composite layer to the titanium nitride layer, reducing interfacial contact resistance.

[0025] The titanium nitride layer, serving as the top protective layer, effectively addresses the issues of repeated SEI film rupture / regeneration and continuous electrolyte consumption, while improving mechanical confinement and electrode rate performance. Titanium nitride is chemically inert and possesses high mechanical strength, allowing it to be directly used as a pre-formed solid electrolyte interface film, isolating the electrolyte from the internal silicon layer and fundamentally preventing the decomposition of organic electrolytes on the silicon surface. Furthermore, the high-modulus titanium nitride layer encapsulates the internal silicon-carbon composite layer, providing radial compressive stress when silicon expands, limiting its outward expansion and reducing internal damage. Moreover, the titanium nitride layer is a metal-like conductor, serving as the top current collector and improving the overall rate performance of the electrode.

[0026] The silicon-based lithium-ion battery anode sheet provided by this invention can form a gradient stress buffer system. The first carbon layer can alleviate the direct pulling on the current collector surface when the silicon-carbon composite layer expands, preventing interface peeling. The carbon layer between the silicon layers can absorb the expansion stress of the adjacent silicon layers, while preventing cracks originating from one silicon layer from propagating to the next layer. The second carbon layer, as an additional flexible buffer layer, homogenizes the uneven expansion stress of the silicon-carbon composite layer before transferring it to the outer titanium nitride layer, preventing the outer hard film from cracking due to excessive local stress. The high-modulus titanium nitride layer wraps around the inner silicon-carbon composite layer, providing radial compressive stress when silicon expands, limiting its outward expansion and reducing internal damage.

[0027] The silicon-based lithium-ion battery anode sheet provided by this invention forms a multi-dimensional electron transport network, improving the rate performance of the entire electrode. The first carbon layer provides a low-resistance electron channel, ensuring that electrons generated by the silicon-carbon composite layer can be quickly transported to the current collector, solving the contact resistance problem caused by the poor conductivity of silicon. Alternating carbon layers within the silicon-carbon composite layer form a three-dimensional conductive framework between the silicon layers, allowing electrons to quickly "jump" through the carbon layers, bypassing the high-resistance silicon bulk. The second carbon layer ensures a smooth electron transport path from the silicon-carbon composite layer to the titanium nitride layer, reducing interfacial contact resistance. The titanium nitride layer, a metal-like conductor, can serve as the top current collector, improving the rate performance of the entire electrode.

[0028] The silicon-based lithium-ion battery anode sheet provided by this invention improves the stability of the chemical and electrochemical interface. The titanium nitride layer isolates the electrolyte from contact with the internal silicon layer, the second carbon layer prevents the upper titanium nitride layer from contacting the lower silicon layer, and the first carbon layer isolates the silicon from contact with the current collector, thus "encapsulating" the silicon in the inert environment of carbon and titanium nitride, allowing only lithium ions to pass through and preventing all side reactions.

[0029] The silicon-based lithium-ion battery anode sheet provided by this invention can improve the initial efficiency of lithium-ion batteries. This is because the stable interface reduces the reduction and decomposition of the electrolyte during the first charge and discharge, and the titanium nitride layer does not undergo an irreversible alloying reaction with lithium, thereby improving the initial coulombic efficiency.

[0030] A first typical embodiment of the present invention provides a silicon-based lithium-ion battery negative electrode sheet, which uses a current collector as a substrate and sequentially stacks a first carbon layer, a silicon-carbon composite layer, a second carbon layer and a titanium nitride layer on the surface of the current collector. The silicon-carbon composite layer consists of multiple alternating silicon and carbon layers.

[0031] In one or more embodiments, the current collector is one of copper foil, nickel foil, copper foam, or nickel foam, preferably copper foil.

[0032] In one or more embodiments, the silicon-carbon composite layer has an alternation period of 8 to 12 cycles between the silicon and carbon layers, and the total thickness of the silicon-carbon composite layer is 70 to 200 nm. Too few cycles result in insufficient buffering, while too many cycles affect the capacity.

[0033] Preferably, the thickness of the silicon layer is 8-12 nm and the thickness of the carbon layer is 2-3 nm in each alternation cycle. When the silicon layer is too thick, its volume expansion is too large, leading to problems such as pulverization and cracking.

[0034] In one or more embodiments, the thickness of the first carbon layer is 4 to 6 nm, preferably 5 nm.

[0035] In one or more embodiments, the thickness of the second carbon layer is 4 to 6 nm, preferably 5 nm.

[0036] In one or more embodiments, the thickness of the titanium nitride layer is 20~50 nm.

[0037] A second typical embodiment of the present invention provides a method for preparing the silicon-based lithium-ion battery negative electrode sheet as described in the first aspect, comprising the following steps: A first carbon layer, a silicon-carbon composite layer, a second carbon layer, and a titanium nitride layer are magnetron sputtered onto the surface of the current collector.

[0038] In one or more embodiments, a method for magnetron sputtering a silicon-carbon composite layer on the surface of a first carbon layer includes: A silicon-carbon composite layer is obtained by sequentially magnetron sputtering a silicon layer and a carbon layer on the surface of the first carbon layer, followed by repeated alternating magnetron sputtering of the silicon and carbon layers.

[0039] Preferably, the number of alternation periods between the silicon layer and the carbon layer is 8 to 12.

[0040] A third typical embodiment of the present invention provides a lithium-ion battery, comprising the silicon-based lithium-ion battery negative electrode sheet described in the first aspect or the silicon-based lithium-ion battery negative electrode sheet prepared by the preparation method described in the second aspect.

[0041] To enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below with reference to specific embodiments.

[0042] Example 1 A silicon-based lithium-ion battery negative electrode sheet, which uses copper foil as a substrate and sequentially stacks a first carbon layer, a silicon-carbon composite layer, a second carbon layer and a titanium nitride layer on the surface of the current collector. The thickness of the first carbon layer is 5 nm; The silicon-carbon composite layer consists of multiple alternating silicon and carbon layers, with 10 alternation cycles. In each alternation cycle, the thickness of the silicon layer is 10 nm and the thickness of the carbon layer is 2 nm. The thickness of the second carbon layer is 5 nm; The thickness of the titanium nitride layer is 30 nm.

[0043] Preparation of silicon-based lithium-ion battery anode sheets: A copper foil (100 mm × 1000 mm) was placed in a sputtering chamber, and a first carbon layer, a silicon-carbon composite layer, a second carbon layer, and a titanium nitride layer were sequentially magnetron sputtered onto the surface of the copper foil.

[0044] The specific process: (1) Place the copper foil (100 mm × 1000 mm) in the sputtering chamber, and evacuate the chamber to a vacuum degree of 10. -6 Pa; after maintaining vacuum pressure for 30 min, high-purity argon gas is introduced, repeated 3 times; finally, the chamber is evacuated to a vacuum degree of 10. -6 Pa; using high-purity graphite as the target material, the distance between the target material and the copper foil is 15 cm; the sputtering power is 40 W; a first carbon layer with a thickness of 5 nm is formed on the surface of the copper foil.

[0045] (2) Using high-purity graphite and high-purity silicon as targets, a silicon layer and a carbon layer were sequentially magnetron sputtered onto the surface of the first carbon layer, respectively. This process was repeated 9 times, alternating between the silicon and carbon layers, with 10 alternation cycles. In each alternation cycle, the thickness of the silicon layer was 10 nm and the thickness of the carbon layer was 2 nm. During the sputtering of the silicon and carbon layers, the distance between the target and the first carbon layer was 15 cm, and the sputtering power was 80 W.

[0046] (3) Using the same method as in step (1), high-purity graphite is used as the target material to sputter a second carbon layer with a thickness of 5 nm on the surface of the silicon-carbon composite layer.

[0047] (4) Using high-purity titanium nitride as the target material, a titanium nitride layer with a thickness of 30 nm is sputtered on the surface of the second carbon layer. During the sputtering process, the distance between the target material and the second carbon layer is 15 cm; the sputtering power is 100 W.

[0048] Example 2 A silicon-based lithium-ion battery negative electrode sheet, which uses copper foil as a substrate and sequentially stacks a first carbon layer, a silicon-carbon composite layer, a second carbon layer and a titanium nitride layer on the surface of the current collector. The thickness of the first carbon layer is 5 nm; The silicon-carbon composite layer consists of multiple alternating silicon and carbon layers, with 8 alternation cycles. In each alternation cycle, the thickness of the silicon layer is 10 nm and the thickness of the carbon layer is 2 nm. The thickness of the second carbon layer is 5 nm; The thickness of the titanium nitride layer is 30 nm.

[0049] Preparation of silicon-based lithium-ion battery anode sheets: A copper foil (100 mm × 1000 mm) was placed in a sputtering chamber, and a first carbon layer, a silicon-carbon composite layer, a second carbon layer, and a titanium nitride layer were sequentially magnetron sputtered onto the surface of the copper foil.

[0050] The specific process: (1) Place the copper foil (100 mm × 1000 mm) in the sputtering chamber, and evacuate the chamber to a vacuum degree of 10. -6Pa; after maintaining vacuum pressure for 30 min, high-purity argon gas is introduced, repeated 3 times; finally, the chamber is evacuated to a vacuum degree of 10. -6 Pa; using high-purity graphite as the target material, the distance between the target material and the copper foil is 15 cm; the sputtering power is 40 W; a first carbon layer with a thickness of 5 nm is formed on the surface of the copper foil.

[0051] (2) Using high-purity graphite and high-purity silicon as targets, a silicon layer and a carbon layer were sequentially magnetron sputtered onto the surface of the first carbon layer, respectively. The magnetron sputtering of the silicon layer and the carbon layer was repeated 9 times, with 10 alternation cycles. In each alternation cycle, the thickness of the silicon layer was 10 nm and the thickness of the carbon layer was 2 nm. During the sputtering of the silicon layer and the carbon layer, the distance between the target and the first carbon layer was 15 cm; the sputtering power was 80 W.

[0052] (3) Using the same method as in step (1), high-purity graphite is used as the target material to sputter a second carbon layer with a thickness of 5 nm on the surface of the silicon-carbon composite layer.

[0053] (4) Using high-purity titanium nitride as the target material, a titanium nitride layer with a thickness of 30 nm is sputtered on the surface of the second carbon layer. During the sputtering process, the distance between the target material and the second carbon layer is 15 cm; the sputtering power is 100 W.

[0054] Example 3 A silicon-based lithium-ion battery negative electrode sheet, which uses copper foil as a substrate and sequentially stacks a first carbon layer, a silicon-carbon composite layer, a second carbon layer and a titanium nitride layer on the surface of the current collector. The thickness of the first carbon layer is 5 nm; The silicon-carbon composite layer consists of multiple alternating silicon and carbon layers, with 12 alternation cycles. In each alternation cycle, the thickness of the silicon layer is 10 nm and the thickness of the carbon layer is 2 nm. The thickness of the second carbon layer is 5 nm; The thickness of the titanium nitride layer is 30 nm.

[0055] Preparation of silicon-based lithium-ion battery anode sheets: A copper foil (100 mm × 1000 mm) was placed in a sputtering chamber, and a first carbon layer, a silicon-carbon composite layer, a second carbon layer, and a titanium nitride layer were sequentially magnetron sputtered onto the surface of the copper foil.

[0056] The specific process: (1) Place the copper foil (100 mm × 1000 mm) in the sputtering chamber, and evacuate the chamber to a vacuum degree of 10. -6 Pa; after maintaining vacuum pressure for 30 min, high-purity argon gas is introduced, repeated 3 times; finally, the chamber is evacuated to a vacuum degree of 10. -6Pa; using high-purity graphite as the target material, the distance between the target material and the copper foil is 15 cm; the sputtering power is 40 W; a first carbon layer with a thickness of 5 nm is formed on the surface of the copper foil.

[0057] (2) Using high-purity graphite and high-purity silicon as targets, a silicon layer and a carbon layer were sequentially magnetron sputtered onto the surface of the first carbon layer, respectively. This process was repeated 9 times, alternating between the silicon and carbon layers, with 10 alternation cycles. In each alternation cycle, the thickness of the silicon layer was 10 nm and the thickness of the carbon layer was 2 nm. During the sputtering of the silicon and carbon layers, the distance between the target and the first carbon layer was 15 cm, and the sputtering power was 80 W.

[0058] (3) Using the same method as in step (1), high-purity graphite is used as the target material to sputter a second carbon layer with a thickness of 5 nm on the surface of the silicon-carbon composite layer.

[0059] (4) Using high-purity titanium nitride as the target material, a titanium nitride layer with a thickness of 30 nm is sputtered on the surface of the second carbon layer. During the sputtering process, the distance between the target material and the second carbon layer is 15 cm, and the sputtering power is 100 W.

[0060] Comparative Example 1 In this comparative example, the lithium-ion battery negative electrode sheet lacks the first carbon layer compared to Example 1.

[0061] A lithium-ion battery negative electrode sheet, which uses copper foil as a substrate and sequentially stacks a silicon-carbon composite layer, a carbon layer and a titanium nitride layer on the surface of the current collector. The silicon-carbon composite layer consists of multiple alternating silicon and carbon layers, with 10 alternation cycles. In each alternation cycle, the thickness of the silicon layer is 10 nm and the thickness of the carbon layer is 2 nm. The thickness of the carbon layer is 5 nm; The thickness of the titanium nitride layer is 30 nm.

[0062] Preparation of silicon-based lithium-ion battery anode sheets: A copper foil (100 mm × 1000 mm) was placed in a sputtering chamber, and a first carbon layer, a silicon-carbon composite layer, a second carbon layer, and a titanium nitride layer were sequentially magnetron sputtered onto the surface of the copper foil.

[0063] The specific process: (1) Place the copper foil (100 mm × 1000 mm) in the sputtering chamber, and evacuate the chamber to a vacuum degree of 10. -6 Pa; after maintaining vacuum pressure for 30 min, high-purity argon gas is introduced, repeated 3 times; finally, the chamber is evacuated to a vacuum degree of 10. -6 Pa; (2) Using high-purity graphite and high-purity silicon as targets, a silicon layer and a carbon layer were sequentially magnetron sputtered onto the surface of the first carbon layer, respectively. This process was repeated 9 times, alternating between the silicon and carbon layers, with 10 alternation cycles. In each alternation cycle, the thickness of the silicon layer was 10 nm and the thickness of the carbon layer was 2 nm. During the sputtering of the silicon and carbon layers, the distance between the target and the copper foil was 15 cm, and the sputtering power was 80 W.

[0064] (3) Using high-purity graphite as the target material, a carbon layer with a thickness of 5 nm was sputtered on the surface of the silicon-carbon composite layer. The distance between the target material and the silicon-carbon composite layer was 15 cm, and the sputtering power was 40 W.

[0065] Using high-purity titanium nitride as the target material, a titanium nitride layer with a thickness of 30 nm was sputtered on the surface of the second carbon layer. During the sputtering process, the distance between the target material and the carbon layer was 15 cm, and the sputtering power was 100 W.

[0066] Comparative Example 2 Compared with Example 1, this comparative example reduces the number of alternation cycles between silicon and carbon layers.

[0067] A silicon-based lithium-ion battery negative electrode sheet, which uses copper foil as a substrate and sequentially stacks a first carbon layer, a silicon-carbon composite layer, a second carbon layer and a titanium nitride layer on the surface of the current collector. The thickness of the first carbon layer is 5 nm; The silicon-carbon composite layer consists of multiple alternating silicon and carbon layers, with 5 alternation cycles. In each alternation cycle, the thickness of the silicon layer is 10 nm and the thickness of the carbon layer is 2 nm. The thickness of the second carbon layer is 5 nm; The thickness of the titanium nitride layer is 30 nm.

[0068] Preparation of silicon-based lithium-ion battery anode sheets: A copper foil (100 mm × 1000 mm) was placed in a sputtering chamber, and a first carbon layer, a silicon-carbon composite layer, a second carbon layer, and a titanium nitride layer were sequentially magnetron sputtered onto the surface of the copper foil.

[0069] The specific process: (1) Place the copper foil (100 mm × 1000 mm) in the sputtering chamber, and evacuate the chamber to a vacuum degree of 10. -6 Pa; after maintaining vacuum pressure for 30 min, high-purity argon gas is introduced, repeated 3 times; finally, the chamber is evacuated to a vacuum degree of 10. -6 Pa; using high-purity graphite as the target material, the distance between the target material and the copper foil is 15 cm, and the sputtering power is 40 W; a first carbon layer with a thickness of 5 nm is formed on the surface of the copper foil.

[0070] (2) Using high-purity graphite and high-purity silicon as targets, a silicon layer and a carbon layer were sequentially magnetron sputtered onto the surface of the first carbon layer, respectively. This process was repeated four times, alternating between the silicon and carbon layers, with 10 alternation cycles. In each alternation cycle, the thickness of the silicon layer was 10 nm and the thickness of the carbon layer was 2 nm. During the sputtering of the silicon and carbon layers, the distance between the target and the first carbon layer was 15 cm, and the sputtering power was 80 W.

[0071] (3) Using the same method as in step (1), high-purity graphite is used as the target material to sputter a second carbon layer with a thickness of 5 nm on the surface of the silicon-carbon composite layer.

[0072] (4) Using high-purity titanium nitride as the target material, a titanium nitride layer with a thickness of 30 nm is sputtered on the surface of the second carbon layer. During the sputtering process, the distance between the target material and the second carbon layer is 15 cm, and the sputtering power is 100 W.

[0073] Comparative Example 3 Compared with Example 1, this comparative example increases the number of alternating cycles of silicon and carbon layers.

[0074] A silicon-based lithium-ion battery negative electrode sheet, which uses copper foil as a substrate and sequentially stacks a first carbon layer, a silicon-carbon composite layer, a second carbon layer and a titanium nitride layer on the surface of the current collector. The thickness of the first carbon layer is 5 nm; The silicon-carbon composite layer consists of multiple alternating silicon and carbon layers, with 20 alternation cycles. In each alternation cycle, the thickness of the silicon layer is 10 nm and the thickness of the carbon layer is 2 nm. The thickness of the second carbon layer is 5 nm; The thickness of the titanium nitride layer is 30 nm.

[0075] Preparation of silicon-based lithium-ion battery anode sheets: A copper foil (100 mm × 1000 mm) was placed in a sputtering chamber, and a first carbon layer, a silicon-carbon composite layer, a second carbon layer, and a titanium nitride layer were sequentially magnetron sputtered onto the surface of the copper foil.

[0076] The specific process: (1) Place the copper foil (100 mm × 1000 mm) in the sputtering chamber, and evacuate the chamber to a vacuum degree of 10. -6 Pa; after maintaining vacuum pressure for 30 min, high-purity argon gas is introduced, repeated 3 times; finally, the chamber is evacuated to a vacuum degree of 10. -6 Pa; using high-purity graphite as the target material, the distance between the target material and the copper foil is 15 cm, and the sputtering power is 40 W; a first carbon layer with a thickness of 5 nm is formed on the surface of the copper foil.

[0077] (2) Using high-purity graphite and high-purity silicon as targets, a silicon layer and a carbon layer were sequentially magnetron sputtered onto the surface of the first carbon layer, respectively. This process was repeated four times, alternating between the silicon and carbon layers, with 10 alternation cycles. In each alternation cycle, the thickness of the silicon layer was 10 nm and the thickness of the carbon layer was 2 nm. During the sputtering of the silicon and carbon layers, the distance between the target and the first carbon layer was 15 cm, and the sputtering power was 80 W.

[0078] (3) Using the same method as in step (1), high-purity graphite is used as the target material to sputter a second carbon layer with a thickness of 5 nm on the surface of the silicon-carbon composite layer.

[0079] (4) Using high-purity titanium nitride as the target material, a titanium nitride layer with a thickness of 30 nm is sputtered on the surface of the second carbon layer. During the sputtering process, the distance between the target material and the second carbon layer is 15 cm, and the sputtering power is 100 W.

[0080] Comparative Example 4 Compared with Example 1, this comparative example lacks a second carbon layer.

[0081] A silicon-based lithium-ion battery negative electrode sheet, which uses copper foil as a substrate and sequentially stacks a carbon layer, a silicon-carbon composite layer and a titanium nitride layer on the surface of the current collector. The thickness of the carbon layer is 5 nm; The silicon-carbon composite layer consists of multiple alternating silicon and carbon layers, with 10 alternation cycles. In each alternation cycle, the thickness of the silicon layer is 10 nm and the thickness of the carbon layer is 2 nm. The thickness of the titanium nitride layer is 30 nm.

[0082] Preparation of silicon-based lithium-ion battery anode sheets: A copper foil (100 mm × 1000 mm) was placed in a sputtering chamber, and a first carbon layer, a silicon-carbon composite layer, a second carbon layer, and a titanium nitride layer were sequentially magnetron sputtered onto the surface of the copper foil.

[0083] The specific process: (1) Place the copper foil (100 mm × 1000 mm) in the sputtering chamber, and evacuate the chamber to a vacuum degree of 10. -6 Pa; after maintaining vacuum pressure for 30 min, high-purity argon gas is introduced, repeated 3 times; finally, the chamber is evacuated to a vacuum degree of 10. -6 Pa; using high-purity graphite as the target material, the distance between the target material and the copper foil is 15 cm, and the sputtering power is 40 W; a carbon layer with a thickness of 5 nm is formed on the surface of the copper foil.

[0084] (2) Using high-purity graphite and high-purity silicon as targets, a silicon layer and a carbon layer were sequentially magnetron sputtered onto the surface of the carbon layer. This process was repeated 9 times, alternating between the silicon and carbon layers, with 10 alternation cycles. In each alternation cycle, the thickness of the silicon layer was 10 nm and the thickness of the carbon layer was 2 nm. During the sputtering of the silicon and carbon layers, the distance between the target and the first carbon layer was 15 cm, and the sputtering power was 80 W.

[0085] (3) Using high-purity titanium nitride as the target material, a titanium nitride layer with a thickness of 30 nm was sputtered on the surface of the silicon-carbon composite layer. During the sputtering process, the distance between the target material and the second carbon layer was 15 cm, and the sputtering power was 100 W.

[0086] Comparative Example 5 Compared with Example 1, this comparative example has the titanium carbide layer removed.

[0087] A silicon-based lithium-ion battery negative electrode sheet, which uses copper foil as a substrate and sequentially stacks a first carbon layer, a silicon-carbon composite layer and a second carbon layer on the surface of the current collector. The thickness of the first carbon layer is 5 nm; The silicon-carbon composite layer consists of multiple alternating silicon and carbon layers, with 10 alternation cycles. In each alternation cycle, the thickness of the silicon layer is 10 nm and the thickness of the carbon layer is 2 nm. The thickness of the second carbon layer is 5 nm.

[0088] Preparation of silicon-based lithium-ion battery anode sheets: A copper foil (100 mm × 1000 mm) was placed in a sputtering chamber, and a first carbon layer, a silicon-carbon composite layer, a second carbon layer, and a titanium nitride layer were sequentially magnetron sputtered onto the surface of the copper foil.

[0089] The specific process: (1) Place the copper foil (100 mm × 1000 mm) in the sputtering chamber, and evacuate the chamber to a vacuum degree of 10. -6 Pa; after maintaining vacuum pressure for 30 min, high-purity argon gas is introduced, repeated 3 times; finally, the chamber is evacuated to a vacuum degree of 10. -6 Pa; using high-purity graphite as the target material, the distance between the target material and the copper foil is 15 cm, and the sputtering power is 40 W to form a first carbon layer with a thickness of 5 nm on the surface of the copper foil.

[0090] (2) Using high-purity graphite and high-purity silicon as targets, a silicon layer and a carbon layer were sequentially magnetron sputtered onto the surface of the first carbon layer, respectively. This process was repeated 9 times, alternating between the silicon and carbon layers, with 10 alternation cycles. In each alternation cycle, the thickness of the silicon layer was 10 nm and the thickness of the carbon layer was 2 nm. During the sputtering of the silicon and carbon layers, the distance between the target and the first carbon layer was 15 cm, and the sputtering power was 80 W.

[0091] (3) Using the same method as in step (1), high-purity graphite is used as the target material to sputter a second carbon layer with a thickness of 5 nm on the surface of the silicon-carbon composite layer.

[0092] Experimental Example 1 The negative electrode sheets provided in Examples 1-3 and Comparative Examples 1-5 were assembled into lithium-ion batteries for battery performance testing.

[0093] Preparation of the positive electrode sheet: Lithium iron phosphate (LiFePO4), a positive electrode active material, superconducting carbon black (SP), a conductive agent, and styrene-butadiene rubber (SBR), a binder, are dispersed in N-methyl-2-pyrrolidone (NMP) solvent at a mass ratio of 96:2:2. The solvent and powder are mixed evenly at a mass ratio of 3:2 to obtain a positive electrode slurry. The positive electrode slurry is uniformly coated on aluminum foil for the positive electrode current collector. After drying, cold pressing, slitting, and die-cutting, a positive electrode sheet is obtained.

[0094] Electrolyte preparation: Ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate were mixed uniformly in a volume ratio of 3:3:4 to obtain a mixed solvent. Lithium hexafluorophosphate (as a lithium salt) and fluoroethylene carbonate were added to the mixed solvent, and the mixture was stirred uniformly to prepare an electrolyte. In this electrolyte, the concentration of lithium hexafluorophosphate was 1.1 mol / L, and the mass percentage of vinylene carbonate was 3%.

[0095] Polyethylene film is used as the diaphragm.

[0096] Lithium-ion battery assembly: The above-mentioned positive electrode, separator, and negative electrode are wound together so that the separator acts as an insulator between the positive and negative electrode. The resulting bare cell is then placed in an outer packaging shell, dried, and injected with electrolyte. After vacuum sealing, a lithium-ion battery cell is obtained.

[0097] The following performance characteristics of lithium-ion batteries were tested.

[0098] (1) Initial capacity utilization: The battery was tested using the Blue Electric testing system for charge and discharge.

[0099] Under 25℃ conditions, the battery charge and discharge voltage range is maintained at 2.5-3.65 V. The battery is cycled at a charge current density of 0.2 C and a discharge current density of 0.1 C. The discharge capacity of the battery in the third cycle is recorded. The mass ratio of the discharge to the active material in the positive electrode is calculated. This ratio is the initial specific capacity. (The first charge cycle of the battery is the formation stage. The third cycle is more stable than the first two cycles. Therefore, the discharge capacity of the third cycle is selected to calculate the initial specific capacity of the battery cell.)

[0100] (2) Cyclic capacity retention rate (100 cycles) A battery testing system was used to perform charge-discharge cycle tests.

[0101] Under conditions of 25℃, the battery charge / discharge voltage range is maintained at 2.5-3.6 V, and the charge / discharge current density is 0.5C. The capacity after the third discharge cycle is recorded as the initial capacity C0, and the capacity after the 100th cycle is recorded as the capacity C. 100 C 100 The ratio of C0 to C0 is the retention rate for the current lap.

[0102] (3) Low-temperature discharge capacity retention rate: The battery was tested using the Blue Electric testing system for charge and discharge.

[0103] Initial charging was performed at 25℃ with a charging current density of 0.5 C and a cutoff voltage of 3.6 V. The battery was then placed in different temperature environments (25℃, 0℃, and -20℃) with a discharge current density of 0.5 C and a cutoff voltage of 2.5 V. The capacity is denoted as C. 25℃ C 0℃ C -20℃ With C 25℃ The ratio is the low-temperature discharge capacity retention rate; (4) Rate discharge capacity retention rate: The battery was tested using the Blue Electric testing system for charge and discharge.

[0104] Initial charging was performed at 25°C with a charging current density of 0.5 C and a cutoff voltage of 3.6 V. The battery was then placed in a 25°C environment with discharge current densities of 0.5 C, 1.0 C, and 2.0 C, and a cutoff voltage of 2.5 V. The capacity is denoted as C. 0.5C C 1C C 2C With C 0.5C The ratio of is the rate discharge capacity retention rate.

[0105] Table 1 shows the specific capacity utilization and initial charge / discharge efficiency of lithium-ion batteries containing the negative electrode sheets provided in Examples 1-3 and Comparative Examples 1-5.

[0106] Table 2 shows the low-temperature discharge capacity retention of lithium-ion batteries containing the negative electrode sheets provided in Examples 1-3 and Comparative Examples 1-5.

[0107] Table 3 shows the rate discharge capacity retention of lithium-ion batteries containing the negative electrode sheets provided in Examples 1-3 and Comparative Examples 1-5.

[0108] Table 1 shows the specific capacity and initial charge / discharge efficiency of the lithium-ion batteries containing the negative electrode sheets provided in Examples 1-3 and Comparative Examples 1-5.

[0109] Table 2 Low-temperature discharge capacity retention of lithium-ion batteries containing the negative electrode sheets provided in Examples 1-3 and Comparative Examples 1-5

[0110] Table 3. Rate discharge capacity retention of lithium-ion batteries containing the negative electrode sheets provided in Examples 1-3 and Comparative Examples 1-5

[0111] Table 4. Room temperature cycle capacity retention of lithium-ion batteries containing the negative electrode sheets provided in Examples 1-3 and Comparative Examples 1-5

[0112] Compared to Example 1, Comparative Example 1 lacks a first carbon layer, resulting in a lower initial coulombic efficiency and an extremely short cycle life.

[0113] Compared to Example 1, Comparative Example 2 reduced the number of alternation cycles between the silicon and carbon layers, resulting in a sharp deterioration in the cycle stability of the battery. In the initial stage of charge and discharge, the capacity was high, but after only 50-100 cycles, the capacity rapidly decreased to less than 80% of the initial value.

[0114] Compared to Example 1, Comparative Example 3 increased the number of alternating cycles of silicon and carbon layers, resulting in a lower initial discharge specific capacity than the theoretical design value, and poor performance at high rates (fast charging).

[0115] Compared with Example 1, Comparative Example 4 lacks a second carbon layer, resulting in a sharp deterioration in the cycle stability of the battery, accompanied by a severe increase in interfacial polarization resistance.

[0116] Compared to Example 1, Comparative Example 5 lacks a titanium carbide layer, resulting in extremely poor cycle life (possibly <50 cycles), low initial coulombic efficiency (<70%), uncontrolled electrode expansion, and severe electrolyte consumption.

[0117] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A silicon-based lithium-ion battery negative electrode, characterized in that, It uses a current collector as the substrate, and sequentially stacks a first carbon layer, a silicon-carbon composite layer, a second carbon layer and a titanium nitride layer on the surface of the current collector. The silicon-carbon composite layer consists of multiple alternating silicon and carbon layers.

2. The silicon-based lithium-ion battery negative electrode sheet as described in claim 1, characterized in that, The current collector is one of copper foil, nickel foil, copper foam, or nickel foam, preferably copper foil.

3. The silicon-based lithium-ion battery negative electrode sheet as described in claim 1, characterized in that, In the silicon-carbon composite layer, the number of alternation periods between silicon and carbon layers is 8 to 12, and the total thickness of the silicon-carbon composite layer is 70 to 200 nm.

4. The silicon-based lithium-ion battery negative electrode sheet as described in claim 3, characterized in that, In each alternation cycle, the thickness of the silicon layer is 8–12 nm, and the thickness of the carbon layer is 2–3 nm.

5. The silicon-based lithium-ion battery negative electrode sheet as described in claim 1, characterized in that, The thickness of the first carbon layer is 4~6 nm, preferably 5 nm.

6. The silicon-based lithium-ion battery negative electrode sheet as described in claim 1, characterized in that, The thickness of the second carbon layer is 4~6 nm, preferably 5 nm.

7. The silicon-based lithium-ion battery negative electrode sheet as described in claim 1, characterized in that, The thickness of the titanium nitride layer is 20~50nm.

8. The method for preparing the silicon-based lithium-ion battery negative electrode sheet according to any one of claims 1 to 7, characterized in that, Includes the following steps: A first carbon layer, a silicon-carbon composite layer, a second carbon layer, and a titanium nitride layer are magnetron sputtered onto the surface of the current collector.

9. The preparation method according to claim 8, characterized in that, The method for magnetron sputtering a silicon-carbon composite layer on the surface of a first carbon layer includes: A silicon-carbon composite layer is obtained by sequentially magnetron sputtering a silicon layer and a carbon layer on the surface of the first carbon layer, and then repeatedly and alternately magnetron sputtering the silicon layer and the carbon layer. Preferably, the number of alternation periods between the silicon layer and the carbon layer is 8 to 12.

10. A lithium-ion battery, characterized in that, Includes the silicon-based lithium-ion battery anode sheet according to any one of claims 1 to 7 or the silicon-based lithium-ion battery anode sheet prepared by the preparation method according to claim 8 or 9.